Draft Genome Sequence of Bradyrhizobium elkanii TnphoA 33, a Producer of Polyhydroxyalkanoates - Lopes, Erica M. [UNESP]; Kishi, Luciano T. [UNESP]; Fernandes, Camila C. [UNESP]; Paganelli, Fernanda Larozza; Alves, Lucia M. C. [UNESP]; Lemos, Eliana G. M. [UNESP]; Marcondes de Souza, Jackson A. [UNESP] (Amer Soc Microbiology, 2017)
The genus Bradyrhizobium comprises bacteria with the ability to form nitrogen-fixing symbioses with legumes. They are of great interest in agriculture, as well as for the production of biopolymers such as polyhydroxyalkanoates. Here, we report the draft genome assembly of Bradyrhizobium elkanii TnphoA 33 comprising 9 Mb, 1,124 contigs, and 9,418 open reading frames.